Prevalence of Refractive Errors Among School-Age Children and Adolescents in Saudi Arabia: A Systematic Review and Meta-Analysis - Al Khathami A; Baklola M; Alshehri AA; Alnasser LH; Alshehri RS; Salawi MA; Alwadai RH; Al Ghazwi M; Alanazi AAQ; Alshammari AM; Al-bawah N; Hafez M; et al. (Clinical Ophthalmology, 2025)
Abdulmajeed Al Khathami,1,* Mohamed Baklola,2,* Anwar Ali Alshehri,3 Lujain Hussain Alnasser,4 Razan Saleh Alshehri,5 Mohammed A Salawi,6 Rahaf Hussain Alwadai,7 Mohammed Al Ghazwi,8 Amira Ahmed Qadim Alanazi,9 Asayel Mojidea Alshammari,10 Naji Al-bawah,11,* Mayas Hafez,12 Abdullah Abu Melha1 1Department of Ophthalmology, King Fahad Hospital, Al Baha Health Cluster, Al Baha, Saudi Arabia; 2Faculty of Medicine, Mansour University, Mansoura, Egypt; 3College of Medicine, University of Bisha, Bisha, Saudi Arabia; 4College of Medicine, University of Hail, Hail, Saudi Arabia; 5Imam Abdulrahman Bin Faisal University, College of Medicine, Dammam, Saudi Arabia; 6College of Medicine, Taif University, Taif, Saudi Arabia; 7College of Medicine, Najran University, Najran, Saudi Arabia; 8Batterjee Medicine college, Jeddah, Saudi Arabia; 9College of Medicine, Northern Border University, Arar, Saudi Arabia; 10College of Medicine, Aljouf University, Aljouf, Saudi Arabia; 11Faculty of Medicine, Sana’a University, Sana’a, Yemen; 12Qatif Central Hospital, Al Qatif, 32654, Saudi Arabia*These authors contributed equally to this workCorrespondence: Naji Al-bawah, Email Najialbawah@gmail.com Mohamed Baklola, Email Mohamedbaklola2000@gmail.comBackground: Refractive errors, including myopia, hyperopia, and astigmatism, are a leading cause of visual impairment among children worldwide. In Saudi Arabia, the prevalence of these conditions among school-age children and adolescents remains poorly understood, with significant variations reported across studies. This systematic review and meta-analysis aimed to provide a comprehensive estimate of the pooled prevalence of refractive errors in this population and explored factors influencing their distribution.Methods: A systematic search of PubMed, Scopus, Web of Science, and ScienceDirect was conducted in accordance with PRISMA 2020 guidelines. Observational studies reporting the prevalence of refractive errors among Saudi school-aged children and adolescents were included. Data extraction and quality assessment were conducted using the Newcastle-Ottawa Scale. Pooled prevalence estimates with 95% confidence intervals (CIs) were calculated using a random-effects model, and heterogeneity was assessed with the I² statistic.Results: Nine studies including over 15,000 participants were analyzed. The pooled prevalence of myopia was 6.7% (95% CI: 3.0% to 14.2%), hyperopia was 3.6% (95% CI: 1.3% to 9.8%), and astigmatism was 7.7% (95% CI: 2.5% to 20.9%). Subgroup analysis revealed regional disparities, with the highest myopia prevalence reported in Taif (33.3%) and Bisha (22.5%), and the lowest in Medina (1.6%). Studies conducted after 2018 showed a significantly higher pooled myopia prevalence (16.4%, 95% CI: 8% to 30.5%) compared to those published before 2018 (3.3%, 95% CI: 1.4% to 7.5%) (p < 0.001). While studies using cycloplegic refraction reported a slightly higher myopia prevalence (7.2%, 95% CI: 4.7% to 11%) than those using non-cycloplegic methods (6.7%, 95% CI: 2.4% to 17.5%), the difference was not statistically significant (p = 0.9). No significant difference was observed between studies with smaller or larger sample sizes, although high heterogeneity persisted across all subgroups.Conclusion: Refractive errors, particularly astigmatism, represent a significant and growing public health issue among Saudi school-aged children and adolescents. The findings underscore the urgent need for standardized diagnostic protocols, including the use of cycloplegic refraction, and the implementation of school-based vision screening programs.Keywords: myopia, hyperopia, astigmatism, refractive errors, children